1962
DOI: 10.1254/jjp.11.151
|View full text |Cite
|
Sign up to set email alerts
|

ELECTROENCEPHALOGRAPHIC STUDIES ON THE ACTION OF RESERPINE, 3, 4-DIHYDROXYPHENYLALANINE AND 5-HYDROXYTRYPTOPHANE IN REFERENCE TO THE EFFECTS OF PRETREATMENT WITH BETA-PHENYLiSOPROPYLHYDRAZINE

Abstract: The release and the depletion of noradrenaline (1) and serotonin (2) in the central nervous system by the administration of reserpine have been already confirmed by many investigators. showed that the sedative effect of reserpine derived from the release and the depletion of serotonin in the central nervous system. Subsequently, they discussed the role of the serotonergic or Hess' trophotropic system on the activity of the central nervous system. Carlsson (7,8), on the contrary, discussed the role of nor adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1964
1964
1985
1985

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Several investigators have classified the normal cortical EEG of an unanesthetized rabbit into the alert, the resting and the mixed pattern (6)(7)(8). In the present experi ment, both the cortical and the hippocampal EEG pattern were taken as a measure to decide the type of basic EEG pattern of unanesthetized rabbits fixed stereotaxically.…”
Section: Basic Patterns Of the Spontaneous Eeg Of Unanesthetized Rabbmentioning
confidence: 99%
“…Several investigators have classified the normal cortical EEG of an unanesthetized rabbit into the alert, the resting and the mixed pattern (6)(7)(8). In the present experi ment, both the cortical and the hippocampal EEG pattern were taken as a measure to decide the type of basic EEG pattern of unanesthetized rabbits fixed stereotaxically.…”
Section: Basic Patterns Of the Spontaneous Eeg Of Unanesthetized Rabbmentioning
confidence: 99%
“…The pretreatment of animals with methamphetamine, caffeine and physostigmine prevented the EEG alterations induced by the carotid warming, while pheniprazine, pipradrol and imipramine did not inhibit them. Kikuchi (6,7) reported that methamphetamine and pheniprazine caused the desynchronized pattern of the spontaneous EEG and that the threshold voltage of recruiting response was elevated by the administration of metham phetamine but not of pheniprazine. These results showed that the central stimulating action of pheniprazine was weaker than that of methamphetamine.…”
Section: ) Pheniprazine (Catron)mentioning
confidence: 99%